Orchids in the era of Grigory von Langsdorff: two golden decades in the history of the botanical exploration of Brazil (1813-1830) - Ossenbach, Carlos (Universidad de Costa Rica, 2018)
The figure of Grigory Ivanovich von Langsdorff was largely neglected by the scientific literature of the 19th and 20th centuries. German-born von Langsdorff was consul of the Russian Empire in Rio de Janeiro. His activities in Brazil from 1813 to 1830 are here described, a time during which his house in Rio and his famous fazenda Mandiocca became the center of scientific activity and the point of attraction for European travellers and naturalists who flocked to Brazil after its frontiers were opened to foreigners in 1808 by King Joao VI of Portugal. Wilhelm Freyreiss, Friedrich Sellow, Maximilian zu Wied-Neuwied, Augustin de Saint-Hilaire, Carl Friedrich Philipp von Martius, Johann Baptist von Spix, Giuseppe Raddi, Johann Baptist Emanuel Pohl, and Ludwig Riedel are among those who explored Brazil impulsed by von Langsdorff and often under his patronage. Their journeys in Brazil culminated in von Langsdorff’s ill-fated expedition to the interior of Brazil between 1822 and 1829, while the epilogue is marked by Langsdorff’s return to Germany, in a state of insanity and no longer able to publish the results of his life-long scientific efforts.